2021
DOI: 10.1093/rheumatology/keaa876
|View full text |Cite
|
Sign up to set email alerts
|

Risk of serious infections in arthritis patients treated with biological drugs: a matched cohort study and development of prediction model

Abstract: Objectives Serious infection is a concern for patients with inflammatory joint diseases treated with biological drugs (bDMARDs). The objectives were to compare risk of serious infection, defined as infection leading to hospitalization, in patients initiating bDMARD treatment with the general population and, second, to develop a simple clinical prediction model and to obtain risk estimates for individual patients. Methods Matc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 31 publications
3
20
0
Order By: Relevance
“…In the last report, the authors reported that the risk of severe infections is moderately increased in users of bDMARDs compared to those receiving csDMARDs. This result is in line with a recent Danish cohort study that demonstrated a hazard ratio for serious infections of 3.7 (95% CI 3.4–4.1) for bDMARDs users compared to non-users [ 22 ]. Studies also suggest that this risk would be higher during the first year after treatment initiation and that patients with a first episode of infection are at a higher risk for subsequent events [ 22 , 23 , 24 ].…”
Section: Discussionsupporting
confidence: 90%
“…In the last report, the authors reported that the risk of severe infections is moderately increased in users of bDMARDs compared to those receiving csDMARDs. This result is in line with a recent Danish cohort study that demonstrated a hazard ratio for serious infections of 3.7 (95% CI 3.4–4.1) for bDMARDs users compared to non-users [ 22 ]. Studies also suggest that this risk would be higher during the first year after treatment initiation and that patients with a first episode of infection are at a higher risk for subsequent events [ 22 , 23 , 24 ].…”
Section: Discussionsupporting
confidence: 90%
“…The few observational studies assessing IRs of SIs in patients with PsA treated with biologicals have reported widespread estimates from 2.7 to 19.6/100 person-years. [8][9][10][11] The IRs found in our analyses are thus in line with these previously reported estimates.…”
Section: Discussionsupporting
confidence: 92%
“…The study was not specifically designed to compare the risk of SIs between patient groups, but concluded that the risk is similar. 11 However, in this study, the follow-up period was defined as 12 months regardless of drug discontinuation, and difference in drug retention between patients with RA and PsA were not accounted for. A study using administrative data found no significant difference in risk between patients with RA, PsA and/or severe psoriasis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations